APLIKASI PENGOLAHAN CITRA SEBAGAI MEDIA PENGENALAN BATIK NUSANTARA - Selao, Ahmad; Sutriani (Fakultas Teknik Universitas Muhammadiyah Parepare, 2021)
In this case the development of clothing from year to year changes in motifs from certain areas. Traditional batik has many types and motifs where each variation contains a meaning that reflects the art of its manufacture, thus leading to a special meaning that is good to see with the many other motifs and variations. This research method uses several sources from the library, references and materials related to this research. The formula is how to design an application that can be used as an interactive batik introduction and the implementation process of this introduction media application can be more interesting. Testing this application using the black box and white box testing methods, the test results are stated that the test has been successful. The results of this study are Image Processing Applications as a Media for Introduction to Batik Nusantara, which helps users in selecting or matching batik cloth models that have been provided by markers easily and attractively.